El juego y su incidencia en el desarrollo socio – afectivo de los niños y niñas de primer año de educación general básica de la escuela “Ciudad de Zumba” parroquia Zumba cantón Chinchipe periodo lectivo 2014-2015. Lineamientos propositivos - Carrion Ochoa, Ximena Josefina (2015)
This thesis relates to: EL JUEGO Y SU INCIDENCIA EN EL DESARROLLO SOCIO – AFECTIVO DE LOS NIÑOS Y NIÑAS DE PRIMER AÑO DE EDUCACIÓN GENERAL BÁSICA DE LA ESCUELA “CIUDAD DE ZUMBA” PARROQUIA ZUMBA CANTÓN CHINCHIPE PERIODO LECTIVO 2014-2015. LINEAMIENTOS PROPOSITIVOS, conducted according to the provisions of the Rules of Academic System of it was Loja National University. The General Objective: To determine the incidence of the Game as a factor Socio-Affective development factor. How it affects the game Affective Development Partner of children of first year of basic general education school " City Zumba " Zumba parish Canton Chinchipe . School period 2014-2015 ? proactive guidelines The methods used for the preparation of this research work were: Scientific, inductive, deductive, analytical, Synthetic, Descriptive, and Statistical Model, the same that served efficiently helps to achieve children the proposed goal. The techniques and instruments used were a teacher surveg of children in the first of Basic General Education First year “Ciudad de Zumba” School Chinchipe canton to establish the type of games that the teacher applies in its Survey Daily Working Hours; assess the Socio-Affective development. According to the results teachers survey representing 100%, it was concluded that games practice with children in the classroom are the motors Games and Traditional Games. According to the results of the test Ebee Leon Gross was determined that 58% investigates children had affective development of Highly Satisfactory, 32% Satisfactory and 10% Unsatisfactory,